Propiverinium picrate - Jerry P. Jasinski; Ray J. Butcher; Q. N. M. Hakim Al-Arique; H. S. Yathirajan; B. Narayana (Acta Crystallographica Section E, 2009)
The title compound [systematic name: 4-(2,2-diphenyl-2-propoxyacetoxy)-1-methylpiperidin-1-ium picrate], C23H30NO3+·C6H2N3O7−, crystallizes as a salt with one cation–anion (propiverinium picrate) pair in the asymmetric unit. A significant number of conformational changes are observed between the crystalline environment of this cation–anion salt and that of a density functional theory (DFT) calculation of the geometry-optimized structure. The angle between the dihedral planes of the two benzyl rings in the propiverinium cation increases by 14.4 (0)° from that of the crystalline environment. The dihedral angles between the mean planes of each of the benzyl rings and the mean plane of the piperidine increase by 2.0 (8) and 12.3 (5)°. The angles between the mean plane of the acetate group and the mean planes of the interconnected piperidine group and the two benzyl rings decrease by 0.2 (1), 7.4 (6) and 3.2 (2)°, respectively. The mean plane of the phenolate group in the anion changes by +22.6 (9), +22.1 (1) and −2.8 (6)° from the mean planes of the piperidine and benzyl rings in the cation, respectively. In the crystal, a bifurcated N—H...(O,O) hydrogen bond and a weak C—H...π ring interaction help to establish the packing. The two O atoms of the p-NO2 group are disordered with occupancies 0.825 (10):0.175 (10).